Nutrition for infants with bronchopulmonary dysplasia: can individualised nutrition be the answer? - Daniel R Gipson; Krystina Gabriel; Catalina Bazacliu (BMJ Nutrition, Prevention & Health)
Bronchopulmonary dysplasia (BPD) is the most common complication of very premature birth, leading not only to lifelong respiratory complications, but also to developmental impairment. While the impact of adequate postnatal growth in mitigating complications of premature birth is well documented, meeting the nutritional needs of premature infants with variable demands that change rapidly with the disease state remains challenging for neonatologists. In the absence of effective treatments, the focus of research in BPD is on preventative strategies addressing ventilation approach, fluid and nutritional support and limiting inflammation. The studies of nutritional support for babies with established BPD are scarce. This paper addresses nutrition preventative strategies, established BPD nutritional needs and the emerging role of artificial intelligence in individualising the nutritional approach for these infants.